Role of intra-abdominal pressure monitoring in the management of patients with blunt injury abdomen - Punyapu, Sridhar; Naredla, Mallesh; Kola, Chandrasekhara Reddy; Adusumilli, Niharika; Gudimetla, Prerana Raju (International Surgery Journal, 2021)
Background: Blunt injury abdomen is associated with significant morbidity and mortality in spite of improved recognition, diagnosis and management. The aim was to study the role of intra-abdominal pressure (IAP) monitoring in the management of patients with blunt injury abdomen. Methods: Hospital based prospective observational study in 77 patients who presented to emergency medicine department with blunt injury abdomen for over a period of 22 months. Age ≥18 years, patients with acute blunt injury abdomen are included in study. Results: Our study population (77 patients) were a group of patients who presented with blunt injury to abdomen, out of which 66 were male (85.70%), 11 were female (14.30%). Most common age group involved in our study was 20-30 years, mean time of presentation to the hospital was 7.40 hours. SBP, DBP, SpO2 decreased significantly as IAP increases. P. R., R. R. increased significantly as IAP increases. U/O decreased significantly as IAP increases. Sr. Cr, B.U. increased significantly as IAP increases. Surgical abdominal decompression had helped in all operated patients to get statistically significant decrement of IAP during initial post-operative hours. 12 patients required ventilator support in surgically intervened group. Mean duration of hospital stay was 8.025 days. Mortality rate in our study was 3.9%. Conclusions: Before development of intra-abdominal hypertension (IAH) and abdominal compartment syndrome (ACS), the potential candidates should be offered surgical decompression at proper time.